PEMIKIRAN PENDIDIKAN TAUHID AHMAD AS-SURKATI DAN IMPLEMENTASINYA TERHADAP PENDIDIKAN DI AL-IRSYAD - Sudarno Shobron; Yuda Dwi Widyantoro (Universitas Muhammadiyah Surakarta, 2020)
The purpose of this study is to describe the thoughts of Sheikh Ahmad As Surkati about monotheism education and the implementation of Sheikh Ahmad As Surkati's thoughts about monotheism education at Al Irsyad Surakarta Junior High School, so that it can be used as a material for consideration in order to improve the quality of conducting monotheism education. This study uses a qualitative type and includes field research (field research), because the data is fully excavated from the field. This study uses an implementative philosophical approach. Sources of data in this study were obtained directly from field research from a number of sources concerning information about the implementation of the thoughts of Sheikh Ahmad As Surkati about monotheism education at the Middle School Al Irsyad Surakarta. Data collection techniques used in this study were through observation, interviews, and documentation. Data analysis was performed descriptively using the inductive method. The results showed that the thoughts of Shaykh Ahmad As Surkati about monotheism education included three main things, ijtihad and taqlid, sunnah and bid'ah and grave pilgrimage and bertawasul to the prophets and saints. The implementation of Shaykh Ahmad As Surkati's thoughts on monotheism education at Al Irsyad Surakarta Junior High School was carried out through habituation and inclusion in the subject matter of Fiqh.